Regional Development Management with Environmental Sustainability Perspective - Mulyani, Lia; Dahlan, Charly; Inayatullah, Muhamad Iqbal; Koharudin, Koharudin; Suganda, Suganda (Universitas Pahlawan Tuanku Tambusai, 2025)
Environmentally friendly development must be oriented towards fulfilling basic human needs, social equity, improving the quality of life, and sustainability, with the vision of improving the quality of life of the community through the development of intelligence, technology, skills, morals, and art in managing natural resources wisely. The success of this vision depends on a development strategy that emphasizes increasing the potential of human resources in optimal use of natural resources through the application of clean technology, engineering science and appropriate technology to produce quality products, as well as supervision and monitoring that ensures development runs according to plans and goals.